2011
DOI: 10.1557/jmr.2010.44
|View full text |Cite
|
Sign up to set email alerts
|

Origin and magnitude of the large piezoelectric response in the lead-free (1–x)BiFeO3xBaTiO3 solid solution

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…1, XRD diffraction peaks at 32°and 39°were fitted well with two Voigt-shaped peaks for both samples. Referring to BiFeO 3 in rhombohedral structure and structural evolution in the BF-BT binary solid solution [17][18][19][20][21][22][23][24], it is concluded that both pure and 0.26 wt% MnO 2 -doped BF69.6-BZT1.4-BT29 samples are crystallized in rhombohedral perovskite structure, of which the splitting degree of the diffraction peaks around 39°are closely associated with rhombohedral distortion degree. Meanwhile, no secondary phases of Bi 25 FeO 39 and Bi 2 Fe 4 O 9 often met in the BiFeO 3 -based systems were detected out, which implies that BZT diffuses into BF-BT lattice and single perovskitetype phase is obtained here, in agreement with previous observations [28][29][30].…”
Section: Structural Characterizationsmentioning
confidence: 95%
See 3 more Smart Citations
“…1, XRD diffraction peaks at 32°and 39°were fitted well with two Voigt-shaped peaks for both samples. Referring to BiFeO 3 in rhombohedral structure and structural evolution in the BF-BT binary solid solution [17][18][19][20][21][22][23][24], it is concluded that both pure and 0.26 wt% MnO 2 -doped BF69.6-BZT1.4-BT29 samples are crystallized in rhombohedral perovskite structure, of which the splitting degree of the diffraction peaks around 39°are closely associated with rhombohedral distortion degree. Meanwhile, no secondary phases of Bi 25 FeO 39 and Bi 2 Fe 4 O 9 often met in the BiFeO 3 -based systems were detected out, which implies that BZT diffuses into BF-BT lattice and single perovskitetype phase is obtained here, in agreement with previous observations [28][29][30].…”
Section: Structural Characterizationsmentioning
confidence: 95%
“…Wherein, XRD measurements showed them to be pseudo-cubic phase. In the studies of composition-dependent structure of BF-BT binary solid solutions, the reported critical composition for structural phase boundary between rhombohedral and pseudocubic phase is very different, of which 0.725BF-0.275BT, 0.67BF-0.33BT, or a transition region between 0.25BT and 0.33BT has been reported till now [17][18][19][22][23][24]. Referring to Figs.…”
Section: Structural Characterizationsmentioning
confidence: 97%
See 2 more Smart Citations
“…While the first publications on bismuth ferrite-barium titanate (BF-BT) are already several years old, 28 there has been recent progress by a number of researchers. Most appealing is the promise for use of BF-BT at high temperatures, not only replacing PZT, but also considerably improving high-temperature capabilities.…”
mentioning
confidence: 99%